2016
DOI: 10.1038/labinvest.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic post-conditioning attenuates acute lung injury induced by intestinal ischemia–reperfusion in mice: role of Nrf2

Abstract: Intestinal ischemic post-conditioning (IPo) protects against lung injury induced by intestinal ischemia-reperfusion (IIR) partly through promotion of expression and function of heme oxygenase-1 (HO-1). NF-E2-related factor-2 (Nrf2) is a key transcription factor that interacts with HO-1 and regulates antioxidant defense. However, the role of Nrf2 in IPo protection of IIR-induced pulmonary injury is not completely understood. Here we show that IPo significantly attenuated IIR-induced lung injury and suppressed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
5
24
0
1
Order By: Relevance
“…This endogenous protective-adaptive intervention suppresses spontaneous Ca 2+ oscillations and inhibits mPTP opening [22], contributing to the maintenance of mitochondrial homeostasis, attenuation of oxidative stress, and alleviation of apoptosis [23]. IPO-induced protection against IR injury has been confirmed in multiple organs [11,19,22]. Consistent with these studies, we found that IPO markedly attenuated IIR injury as characterized by reduced histological damage and lower levels of serum biomarkers.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This endogenous protective-adaptive intervention suppresses spontaneous Ca 2+ oscillations and inhibits mPTP opening [22], contributing to the maintenance of mitochondrial homeostasis, attenuation of oxidative stress, and alleviation of apoptosis [23]. IPO-induced protection against IR injury has been confirmed in multiple organs [11,19,22]. Consistent with these studies, we found that IPO markedly attenuated IIR injury as characterized by reduced histological damage and lower levels of serum biomarkers.…”
Section: Discussionsupporting
confidence: 86%
“…We previously demonstrated that IPO protects the intestine and remote organs from IIR injury [19,20]. In the present study, we demonstrated that IPO-induced autophagy had a crucial protective role against IIR injury.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nrf2 is also believed to protect a number of organs against IIR injury [22] including the lungs [23]. Furthermore, in several studies, the upregulation of Sirt1 has been found to activate Nrf2 [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…2 İskemik akut böbrek hasarı, nadiren izole olarak ortaya çıkar ve çoğu zaman organ yetmezliklerine neden olur. Akciğer infl amasyonu, çoklu iskemi reperfüzyon hasarının neden olduğu en yaygın komplikasyondur [3][4][5] ve pulmoner yetmezlik akut böbrek hasarı ile ilişkili mortalitenin önde gelen nedenlerinden biridir. 6,7 Akut böbrek hasarı, kritik hastalarda sıklıkla akut akciğer hasarına yol açar.…”
Section: Introductionunclassified